Pengaruh Reputasi Auditor, Ukuran Perusahaan,Likuiditas, Financial Distress Dan Opini Audit TahunSebelumnya Terhadap Penerimaan Opini Audit GoingConcern(Studi Pada Perusahaaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2010-2014) - Prasetyo, Widhy Hastoro Bayu; , Dra Rina Trisnawati, Ak, M,Si, PhD (2016)
Going concern audit opinion is one thing into consideration the users of financial statements to make decisions in investing. Going concern audit opinion received by a firm showing that their auditors will doubt the survival of the company. This study was conducted to determine the effect of auditor reputation, company size, liquidity, financial distress and prior year's audit opinion on going concern audit opinion. This study was performed on companies listed in Indonesia Stock Exchange 2010-2014. The sampling method using purposive sampling. Through logistic regression analysis on the sample size of this study as many as 24 companies in accordance with predetermined criteria. Based on the results of analysis show that variables prior year's audit opinion is significantly and positively on a going-concern audit opinion. As for variable reputation of auditors, company size, liquidity, and financial distress had no significant effect on the going concern audit opinion